Diurnal emission of herbivore-induced (Z)-3-hexenyl acetate and allo-ocimene activates sweet potato defense responses to sweet potato weevils - Yang-yang XIAO; Jia-jia QIAN; Xing-liang HOU; Lan-ting ZENG; Xu LIU; Guo-guo MEI; Yin-yin LIAO (Journal of Integrative Agriculture, 2023)
The sweet potato weevil (Cylas formicarius (Fab.) (Coleoptera: Brentidae)) is a pest that feeds on sweet potato (Ipomoea batatas (L.) Lam. (Solanales: Convolvulaceae)), causing substantial economic losses annually. However, no safe and effective methods have been found to protect sweet potato from this pest. Herbivore-induced plant volatiles (HIPVs) promote various defensive bioactivities, but their formation and the defense mechanisms in sweet potato have not been investigated. To identify the defensive HIPVs in sweet potato, the release dynamics of volatiles was monitored. The biosynthetic pathways and regulatory factors of the candidate HIPVs were revealed via stable isotope tracing and analyses at the transcriptional and metabolic levels. Finally, the anti-insect activities and the defense mechanisms of the gaseous candidates were evaluated. The production of (Z)-3-hexenyl acetate (z3HAC) and allo-ocimene was induced by sweet potato weevil feeding, with a distinct circadian rhythm. Ipomoea batatas ocimene synthase (IbOS) is first reported here as a key gene in allo-ocimene synthesis. Insect-induced wounding promoted the production of the substrate, (Z)-3-hexenol, and upregulated the expression of IbOS, which resulted in higher contents of z3HAC and allo-ocimene, respectively. Gaseous z3HAC and allo-ocimene primed nearby plants to defend themselves against sweet potato weevils. These results provide important data regarding the formation, regulation, and signal transduction mechanisms of defensive volatiles in sweet potato, with potential implications for improving sweet potato weevil management strategies.